Implementation of Online Marketing Strategies in Apen Grocery Shops as A Solution to Facing Competition and The Covid-19 Pandemic Crisis - Himawati, Ditiya; Nurcahyo, Bagus; Saputri , Ika Puji; revena, Ravena (Universitas Ahmad Dahlan, 2023)
Background: Marketplace make it very easy for customers to meet their needs besides that, it is also a means for SMEs to be able to survive facing competition and the Covid 19 pandemic crisis, so this is one of the challenges for sellers who sell offline. An example of offline sales is traditional market traders. This community service (public servant) was carried out at one of the basic food shops located in traditional markets, namely Apen Groceries. Apen Groceries Storeis a shop that provides staple goods located in Pasar Kebayoran Lama, South Jakarta. Apen Groceries Storeis a shop that is in a traditional market, so Apen Groceries Storehas challenges that must be faced, including competitors in modern markets (supermarkets) and online sales, as well as the Covid 19 pandemic situation which is still ongoing today where these conditions are very limiting space for the conventional Apen Shop business. Contribution: This public servant activity contributes to small and medium businesses, in this case the Apen Grocery Store. Method: Implementing online marketing strategies using social media applications and e-marketplaces (such as whatsapp, Instagram and the Shopee application). Results: The results obtained include sales forecasting, namely being able to estimate whether the number of customers will be sufficient with the existing stock or even less, so that they can monitor the product. Conclusion: Grocery stores can already sell their products with offline and online access, namely with the help of social media and e-marketplaces